(untitled) (Annals of Medical Research, 2026)
Aim: Pediatric neurogenic bladder (NB) jeopardizes both lower and upper urinary tract integrity. This study evaluated the pressure-lowering efficacy of intradetrusor botulinum toxin A (BTX-A) in children with spinal-origin NB and identified clinical and urodynamic predictors of treatment response. Materials and Methods: In this retrospective cohort study, 38 pediatric patients with spinal-origin NB who received 100 IU of BTX-A between October 2023 and December 2024 were analyzed. BTX-A was injected cystoscopically at 20 detrusor sites, sparing the trigone. The primary outcome was the 6-month change in storage-phase detrusor pressure (Δp_det), calculated as p_det = p_ves − p_abd per ICCS standards. Secondary outcomes included an exploratory responder endpoint (≥10 cmH₂O reduction in storage pressure) and attainment of guideline-based safe storage thresholds (<30 and <35 cmH₂O). Associations with demographic, functional, and renal parameters were examined using correlation, multivariable regression, and ROC analyses. Results: Mean baseline storage-phase detrusor pressure was 59.9 ± 21.2 cmH₂O, decreasing to 52.5 ± 19.7 cmH₂O at six months (Δp_det = −7.4 ± 12.5 cmH₂O; P < 0.05). A ≥10 cmH₂O reduction in pressure was observed in 26.3% (10/38) of patients, and 10.5% and 13.2% achieved storage pressures <30 cmH₂O and <35 cmH₂O, respectively. In exploratory logistic regression, higher baseline p_det (OR = 1.05; P = 0.039) and preserved renal function (eGFR; OR = 1.04; P = 0.042) were associated with a ≥10 cmH₂O reduction, whereas etiology and age showed non-significant trends. Conclusion: Intradetrusor BTX-A produced a modest but statistically significant reduction in storage-phase detrusor pressure, with only a minority of patients reaching guideline-defined safe storage thresholds. These findings support BTX-A as a clinically relevant pressure-lowering option within a multimodal, pressure-guided strategy — particularly in children with high baseline pressures and preserved renal reserve — rather than as a uniformly transformative stand-alone therapy.